From leader to peer – specializing physicians’ understanding of their multiple positions in interprofessional health care teams - Emma Sallinen; Leena Mikkola; Stephanie Fox; Heli Parviainen (Medical Education Online)
Introduction This exploratory qualitative study aims to uncover the identity work in interprofessional (IP) team interaction to understand specializing physicians’ (SP) professional identities by analyzing how they position themselves in relation to others through the lens of positioning theory.Method The data for this study consist of 65 self-reflexive essays written by SPs during their mandatory leadership studies.Results Altogether, five distinct physician positions (peer, coordinator, leader, medical expert, and decision-maker) and two distinct storylines (teamwork as communication vs. teamwork as an organizational tool) were identified during the positioning analysis.Discussion The wide range of physician positions reveals how diversely and dynamically SPs adapt leadership as part of their professional identity and reframes future studies to explore how SPs construct the dimensions of their professional identity rather than whether they do so.